2022
DOI: 10.3389/fnut.2022.825913
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Dietary Zinc Intake and Metabolic Syndrome. A Meta-Analysis of Observational Studies

Abstract: BackgroundEpidemiological studies have investigated the association between dietary zinc intake and metabolic syndrome (MetS). However, their results are conflicting. This meta-analysis was therefore employed to investigate the associations further.MethodsA comprehensive literature search was employed by using the electronic database of PubMed, Web of Science, and Embase up to November 2021. The pooled relative risk (RR) of MetS for the highest vs. lowest dietary zinc intake category, and the weighted mean dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 51 publications
0
1
1
1
Order By: Relevance
“…This may indicate that selenium itself is not deficient among U.S. adults and that excessive selenium intake contributes to selenium toxicity. A recent meta-analysis suggested that dietary zinc intake was negatively associated with the prevalence of MetS, contrary to our findings ( Ding et al, 2022 ). A previous analysis of a cohort from China showed that dietary zinc intake was associated with lower blood pressure and FPG in female subjects, but increased TG levels in all Chinese participants ( Wang et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…This may indicate that selenium itself is not deficient among U.S. adults and that excessive selenium intake contributes to selenium toxicity. A recent meta-analysis suggested that dietary zinc intake was negatively associated with the prevalence of MetS, contrary to our findings ( Ding et al, 2022 ). A previous analysis of a cohort from China showed that dietary zinc intake was associated with lower blood pressure and FPG in female subjects, but increased TG levels in all Chinese participants ( Wang et al, 2018 ).…”
Section: Discussioncontrasting
confidence: 99%
“…These ndings are in agreement with previous studies. [31][32][33] A pro-in ammatory diet can lead to increased levels of circulating in ammatory cytokines such as IL-1β, IL-6, TNF-α, and CRP, [20] which are associated not only with the metabolic disorders it causes (hyperinsulinemia, insulin resistance, dyslipidemia, hyperglycemia, and hypertension), but also with the resulting dysbiosis of the intestinal ecology, increased intestinal permeability, intestinal barrier dysfunction, and leakage of toxic bacterial metabolites into the circulatory system. [8] [34] This induction and ampli cation of systemic in ammation by a pro-in ammatory diet is considered to be related to cognitive impairment.…”
Section: Discussionmentioning
confidence: 99%
“…Цинк -микроэлемент, участвующий в регуляции продукции воспалительных цитокинов, контроле окислительного стресса и регуляции иммунных ответов. МК, выступающая основным антиоксидантом в плазме крови человека или прооксидантом внутри клетки, может быть связана с цинком, способным замедлять окислительный процесс [45]. Цинк присутствует в морепродуктах, красном мясе и птице, цельнозерновых и молочных продуктах, печеных бобах, нуте и орехах.…”
Section: цинкunclassified